Hubungan Status Gizi dan Pola Makan Terhadap Kejadian Anemia pada Ibu Hamil Trimester III di Wilayah Kerja Puskesmas Tanjung Enim - Kevin Merdayanti; Ahmad Fauzi (Universitas Malahayati Lampung, 2024)
ABSTRACT Women of childbearing age (WUS) are women whose reproductive organs are functioning properly between the ages of 20-45 years. Age of fertility is in the range of 20-29 years. At this age a woman has a 95% chance of getting pregnant. The prevalence of anemia at the Tanjung Enim Health Center in January - March 2019 was 71 pregnant women. In April-May the researchers found 30 pregnant women with anemia which was quite high. To determine the relationship between nutritional status and diet on the incidence of anemia in pregnant women at the Tanjung Enim Health Center in 2023. This research is an analytic study with a cross-sectional or survey study design. The population that became the object of this study were pregnant women who were in Trimesters 1, 2 and 3 as well as pregnant women who suffered from anemia and those who did not suffer from anemia at the Tanjung Enim Health Center. The research sample was taken using simple random sampling. Data analysis used univariate analysis of frequency distribution and bivariate Spearman rank analysis. The results of the Speramean Rank correlation test for nutritional status obtained P-Value 0.04 0.05. The results of the Spearmean Rank correlation test for eating patterns obtained a P-Value of 0.000 0.05. There is a relationship between nutritional status and eating pattern with the incidence of anemia in third trimester pregnant women at the Tanjung Enim Health Center. Keywords: Nutritional Status, Diet, Anemia ABSTRAK Wanita usia subur (WUS) adalah wanita yang keadaan organ reproduksinya berfungsi dengan baik antara umur 20-45 tahun. Usia kesuburan ada pada rentang 20-29 tahun. Pada usia ini wanita memiliki kesempatan 95% untuk hamil. Prevalensi anemia di Puskesmas Tanjung Enim pada bulan Januari - Maret 2019 sebanyak 71 ibu hamil. Pada bulan April – Mei peneliti mendapatkan 30 ibu hamil dengan anemia yang terbilang cukup tinggi. Tujuan untuk mengetahui hubungan antara satus gizi dan pola makan terhadap kejadian anemia pada ibu hamil di Puskesmas Tanjung Enim tahun 2023. Penelitian ini adalah studi analitik dengan desain studi cross-sectional atau survei. Populasi yang menjadi objek penelitian ini adalah ibu hamil yang berada di Trimester 1, 2, dan 3 serta ibu hamil yang menderita anemia dan yang tidak menderita anemia di Puskesmas Tanjung Enim. Sampel penelitian yang diambil menggunakan simple random sampling Analisis data menggunakan analisis univariat distribusi frekuensi dan analisis bivariat spearman rank. Hasil uji korelasi Speramean Rank status gizi diperoleh P-Value 0.04 0.05. Hasil uji korelasi Spearmean Rank pola makan diperoleh P-Value 0.000 0.05. Terdapat hubungan Status Gizi dan pola makan dengan Kejadian Anemia Ibu Hamil Trimester III di Puskesmas Tanjung Enim. Kata Kunci: Status Gizi, Pola Makan, Anemia